Endometriosis and Cardiovascular Disease: A Systematic Review - Pande Putu Firsta Widyaning (Asian Journal of Health Research, 2024)
Introduction: Endometriosis is a chronic condition characterized by the aberrant distribution of functional tissue outside of the uterus, such as endometrial ducts and stroma. It is dependent on estrogen. Cardiovascular disease may be more prevalent in women who have endometriosis. Materials/Methods: Using the following keywords: "atherosclerosis," "cardiovascular disease," "cardiovascular risk," "chronic inflammation," "dyslipidaemia," "endometriosis," and "endothelial dysfunction," we searched for publications published between 2017 and 2022. A thorough literature search was conducted using a variety of search engines, such as PubMed, Cochrane, Springer, Science Direct, Nature, and Google Scholar. The literature selection was conducted using the recommendations of the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P).. Results: In women with endometriosis, four studies reported an elevated risk and incidence of cerebrovascular disease and cardiovascular disease. A study reported a substantial increase in the lipid profile value of patients with endometriosis, a known risk factor for the development of atherosclerosis. Conclusion: Cardiovascular disease is more likely to strike women who have endometriosis.